Magnetic moment and local magnetic induction of superconducting/ferromagnetic structures subjected to crossed fields: experiments on GdBCO and modelling. (12th October 2016) - Fagnard, J F; Morita, M; Nariki, S; Teshima, H; Caps, H; Vanderheyden, B; Vanderbemden, P
Abstract: Recent studies have shown that ferromagnetic materials can be used together with bulk high temperature superconductors in order to improve their magnetic trapped field. Remarkably, it has also been pointed out that ferromagnets can help in reducing the crossed field effect, namely the magnetization decay that is observed under the application of AC transverse magnetic fields. In this work, we pursue a detailed study of the influence of the geometry of the ferromagnetic part on both trapped fields and crossed field effects. The magnetic properties of the hybrid superconducting/soft ferromagnetic structures are characterized by measuring the magnetic moment with a bespoke magnetometer and the local magnetic field density with Hall probes. The results are interpreted by means of 2D and 3D numerical models yielding the distribution of the superconducting currents as a function of the ferromagnet geometry. We examine in details the distortion of the shielding superconducting currents distribution in hybrid structures subjected to crossed magnetic fields. These results confirm the existence of an optimum thickness of the ferromagnet, which depends on the saturation magnetization of the ferromagnetic material and the current density of the superconductor. A hybrid structure providing an efficient protection against the crossed magnetic field while maintaining the magnetic induction along the axis of the structure is suggested. The limitations of the 2D modelling in this configuration are discussed.